2023
DOI: 10.3389/fphys.2023.1228476
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiopulmonary interactions in development of ventilator-induced lung injury—Experimental evidence and clinical Implications

Abstract: Ventilator-induced lung injury (VILI) impacts outcomes in ARDS and optimization of ventilatory strategies improves survival. Decades of research has identified various mechanisms of VILI, largely focusing on airspace forces of plateau pressure, tidal volume and driving pressure. Experimental evidence indicates the role of adverse cardiopulmonary interaction during mechanical ventilation, contributing to VILI genesis mostly by modulating pulmonary vascular dynamics. Under passive mechanical ventilation, high tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The present data also supported this finding, indicating that the association between OSI values and mortality was mediated by ARDS. Critically ill patients with ARDS experienced a decline in pulmonary compliance and an increase in nonaerated compartments, potentially making them more susceptible to VILI [ 71 , 72 ]. Previous studies have also demonstrated that ARDS patients with higher OSI values exhibited higher mortality, which was further validated in the present study [ 5 , 20 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present data also supported this finding, indicating that the association between OSI values and mortality was mediated by ARDS. Critically ill patients with ARDS experienced a decline in pulmonary compliance and an increase in nonaerated compartments, potentially making them more susceptible to VILI [ 71 , 72 ]. Previous studies have also demonstrated that ARDS patients with higher OSI values exhibited higher mortality, which was further validated in the present study [ 5 , 20 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of PEEP increase the pulmonary vascular resistance that governs right ventricular (RV) afterload, while simultaneously raising pleural and central venous pressures to impede systemic venous return and limit right ventricular preload [27,28 ▪ ]. Without compensatory recruitment of the vascular bed, raising PEEP augments PVR and the ejection impedance confronting the afterload-sensitive RV, especially in the setting of ARDS [28 ▪ ]. Indeed, cor pulmonale has been reported to occur in approximately one quarter of such patients with acute lung injury [29].…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…Higher levels of PEEP not only raise PVR but also increase the vascular pressure gradient across the alveolus, with the potential to modulate alveolar stress and strain. A greater microvascular pressure difference predisposes to edema formation, and under certain ventilatory conditions, a heightened vascular gradient also augments endothelial shear and promotes the expression of VILI [28 ▪ ,31]. Small animal experiments demonstrate that when tidal airway pressures are high, raising precapillary vascular pressures or lowering postcapillary pressures dramatically worsen erythrocyte extravasation and other histologic signs of rupture of the blood-gas barrier.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%